Bitter peptides from enzymatically hydrolyzed protein increase the number of leucocytes and lysozyme activity of large yellow croaker (Larimichthys crocea). Issue 81 (October 2018) - Luo, Cheng; Gwekwe, Blessing; Choto, Phares; Miao, Wenhua; Chen, Meiling; Xue, Changfeng; Xu, Yunsheng; Yin, Xiaolong; Magawa, Glory; Wu, Di; Akida, Jamal S.; Wang, Likui; et al.
Abstract: The large yellow croakers ( Larimichthys crocea ) are mainly present in the Chinese coast and near seas with high economic importance, but vulnerable to many diseases, especially in the breeding and aquaculture. The purpose of this research was to boost the innate immune system of the large yellow croaker by administering bitter peptides into their peritoneal cavity. Total 120 Juvenile of large yellow croakers in very even weight of 60 g were divided into 4 different groups in 200/300 L of water tank, respectively. Fish growth were observed for 3 months before and after different treatments. The bitter peptides from pepsin hydrolysis were applied because they possess the highest bitter sensory scores. The blood of fish from the different groups was collected and tested for different immune parameters to evaluate the effectiveness of bitter peptides as immune stimulants after administration for 8 weeks. The average ratio of leukocytes/total blood cells (%) for control was found at 14.6%, for the low dose of bitter peptides 0.6 mg/fish was at 29.3%, for middle dose of 1.2 mg/fish was at 35%, and high dose of 2.4 mg/fish was at 30%. The lysozyme assay showed that the OD (optical density) units of relative progress lysis activity at 60 min were 0.17, 0.101, 0.307 and 0.198, respectively. Similarly in the same order as in phagocyte assay, most importantly the middle dose (1.2mg/fish) gave the highest survival rate throughout the assay. The results showed that bitter peptides can be used as immune boosters for the yellow croakers and the optimum dose was 1.2 mg/fish due to both leukocytes and lysozyme activity in the treated samples increased significantly compared with the control group. According to the results obtained, we suggest that the incorporation of middle dose of bitter peptides into fish feeds may reduce the fish diseases in aquaculture, at least for large yellow croakers. Highlights: Pepsin generated bitter peptides. Bitter peptides increase leukocytes and phagocytosis. Bitter peptides increase plasma lysozyme activity. Middle dose of bitter peptides extend large yellow croakers survival rate.